2011
DOI: 10.1007/s12034-011-0039-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization on strength and toughness of welded joint for Q550 steel

Abstract: Q550 high strength steel was welded using gas shielded arc welding and three different welding wires without pre-or post-heat treatments. The paper investigates the influence of welding wire on the microstructure, tensile strength and impact toughness of Q550 steel weld joints. Results showed that the microstructure of the weld metal of joints produced using ER50-6 wire was a mixture of acicular ferrite and grain boundary ferrite including pro-eutectoid ferrite and ferrite side plate. Acicular ferrite was main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
4

Year Published

2013
2013
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 10 publications
0
5
0
4
Order By: Relevance
“…It is observed that smaller diameter electrodes increase heat input that leads to coarsening of grains results brittleness of joint. The higher heat input also produces significant variation in microstructure of WM and HAZ, thus coarsening of grains take place that lead to deterioration of tensile and impact strength and increase in hardness [ 61 ]. Therefore, it is crucial to restrict the heat input of welding to limited range.…”
Section: Resultsmentioning
confidence: 99%
“…It is observed that smaller diameter electrodes increase heat input that leads to coarsening of grains results brittleness of joint. The higher heat input also produces significant variation in microstructure of WM and HAZ, thus coarsening of grains take place that lead to deterioration of tensile and impact strength and increase in hardness [ 61 ]. Therefore, it is crucial to restrict the heat input of welding to limited range.…”
Section: Resultsmentioning
confidence: 99%
“…Notadamente, devido ao seu pequeno tamanho de grão e aos contornos de alto ângulo que consomem mais energia na propagação de trinca antes da fratura [24]. O desempenho do metal de solda depende de sua microestrutura, à qual é influenciada pela composição química e parâmetros de soldagem [25].…”
Section: Caracterização Microestruturalunclassified
“…Isso caracterizaria uma expectativa de ocorrência de valores de tenacidade muito superiores ao do passe interno devido à reconhecida capacidade desse constituinte em contribuir para a melhoria da tenacidade ao impacto do metal de solda, (8)(9)(10)(11)(12)(13)(14)(15)(16) notadamente devido ao seu pequeno tamanho de grão e aos contornos de alto ângulo que consomem mais energia na propagação de trinca antes da fratura. (11,12) De fato, segundo Zhang et al, (11) o desempenho do metal de solda depende de sua microestrutura, a qual é influenciada pela composição química e parâmetros de soldagem.…”
Section: Análise Metalográficaunclassified
“…Isso caracterizaria uma expectativa de ocorrência de valores de tenacidade muito superiores ao do passe interno devido à reconhecida capacidade desse constituinte em contribuir para a melhoria da tenacidade ao impacto do metal de solda, (8)(9)(10)(11)(12)(13)(14)(15)(16) notadamente devido ao seu pequeno tamanho de grão e aos contornos de alto ângulo que consomem mais energia na propagação de trinca antes da fratura. (11,12) De fato, segundo Zhang et al, (11) o desempenho do metal de solda depende de sua microestrutura, a qual é influenciada pela composição química e parâmetros de soldagem. Com o objetivo de obter juntas soldadas de aços baixa liga com propriedades mecânicas satisfatórias, é necessário conseguir um metal de solda com elevada proporção de ferrita acicular, constituinte microestrutural que apresenta contornos de alto ângulo e alta densidade de discordâncias, o que dificulta a propagação de trincas, fazendo com que a ferrita acicular no metal de solda permita a obtenção da combinação ótima de resistência e tenacidade ao impacto, concordando com as afirmações de Qinglei et al (12) No entanto, observa-se que tal fato Marouço et al Estudo do aporte térmico nas propriedades mecânicas de metais de solda de aço C-Mn obtidos pelo processo arco submerso…”
Section: Análise Metalográficaunclassified
See 1 more Smart Citation